(untitled) (Western European Journal of Historical Events and Social Science, 2025)
The Republic of Uzbekistan is developing the tourism industry as one of the priority areas of the economy. An increase in the quality of hotel services directly affects the increase in the number of tourists, their positive impression of the country, and the sustainable growth of the tourism industry. This article analyzes the methods for measuring the quality of service and customer satisfaction in hotels in Uzbekistan. The study considers the advantages of using methods based on SERVQUAL, HOLSERV, and the Likert scale, and ways to adapt them to the conditions of Uzbekistan. The results show that the main dimensions of service provision — reliability, responsiveness, trustworthiness, empathy, and material environment — directly affect the level of customer satisfaction. Systematic assessment of these dimensions in Uzbek hotels will strengthen customer trust and help bring the quality of service into line with international standards.